Atrial Infarct: An Easily Missed Reality with Hidden Threat A case report with Review of Literature (Cardiovascular Journal, 2015)
Atrial infarction is a very rare diagnosis. Though available literature suggests, the condition per se may have been not so rare. Over the past few decades, atrial infarction have been reported several times, even some case series have been reported, but there is no consensus on the diagnosis of this condition, and its true importance also has not been understood completely. Previous works have shown that this condition is associated with several serious complications; hence recognition of this condition in early period is important, which is at the same time not so easy due to subtlety of the known features and less availability of information. We report a case of 70 year old Muslim, Bengali, male suffering from acute coronary syndrome, in whom, right atrial infarction was recognized by electrographic features, which is very rarely diagnosed with confidence in ante-mortem patients. Since, in Bangladesh, post-mortem autopsy to find out causes behind cardiac death is not done routinely and in the light of possibility of serious life-threatening complications, ante-mortem diagnosis of atrial infarction is necessary. So, Cardiologists should be aware of this uncommon condition.Cardiovasc. j. 2015; 8(1): 65-68